2015
DOI: 10.4081/vsd.2015.6017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aflatoxin B1 and silymarin-containing milk thistle seeds on ileal morphology and digestibility in broiler chickens

Abstract: This study investigated the effects of aflatoxin B1 (AFB1) and milk thistle seed (MTS) on some apparent ileal morphology and digestibility variables in the small intestines of broilers. A total of 216 Ross 308 male broiler chickens were allocated in a 3 3 factorial arrangement of the treatments with three concentration of AFB1 (0, 250, and 500 ppb) and three levels of MTS (0, 5, and 10 g kg -1 ). On day 35, the birds that received diets with 500 ppb of AFB1 alone (main effect) showed significant decrease in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…To our knowledge, no experiments have investigated the effects of silybin on nutrient digestibility in dogs. The literature does, however, discuss these effects in other animals: One report suggests that Silybum marianum (L.) as source of silymarin has no effect on nutrient digestibility in buffalos [22], while an experiment with broiler chickens incorporating S. marianum seeds into the diet resulted in increased nutrient digestibility in terms of mycotoxin-contaminated feed [23]. The present study found no clinically signi cant differences in hematological parameters between the groups of dogs.…”
Section: Discussioncontrasting
confidence: 58%
“…To our knowledge, no experiments have investigated the effects of silybin on nutrient digestibility in dogs. The literature does, however, discuss these effects in other animals: One report suggests that Silybum marianum (L.) as source of silymarin has no effect on nutrient digestibility in buffalos [22], while an experiment with broiler chickens incorporating S. marianum seeds into the diet resulted in increased nutrient digestibility in terms of mycotoxin-contaminated feed [23]. The present study found no clinically signi cant differences in hematological parameters between the groups of dogs.…”
Section: Discussioncontrasting
confidence: 58%
“…In a study by Hasheminejad et al. ( 2015 ), supplementation of two concentrations of SM seeds (5 and 10 g/kg) in broiler diets did not affect villus height or length, crypt depth, goblet cell number, and ratio of villus height to crypt depth.…”
Section: Resultsmentioning
confidence: 89%
“…The morphological characteristics of the jejunum are presented in Thickness of muscle layer and villus height to crypt depth ratio were highest in the treatment with 500 mg/kg CS and 250 mg/kg SM and the lowest in the treatment with 250 mg/kg of both supplements. In a study by Hasheminejad et al (2015), supplementation of two concentrations of SM seeds (5 and 10 g/kg) in broiler diets did not affect villus height or length, crypt depth, goblet cell number, and ratio of villus height to crypt depth.…”
Section: Morphological Characteristics Of Jejunummentioning
confidence: 90%
“…Certainly in our experiment, there was a tendency to an restored goblet cells to normal levels and size when propolis was administered to Aflatoxin-B1 exposed rats. It had been found that intestinal crypt depth (but not villus length) increased linearly with increasing Aflatoxin-B1 concentration [24].…”
Section: Intestinal Absorption Of D-xylosementioning
confidence: 99%